2015
DOI: 10.1007/s12517-015-1890-8
|View full text |Cite
|
Sign up to set email alerts
|

Site response assessment at the city of Al Khobar, eastern Saudi Arabia, from microtremor and borehole data

Abstract: Al Khobar City is affected by distant earthquakes from the Zagros fold-fault belt, which is part of the subduction zone between the Arabian and Eurasian plates. These earthquakes have generated substantial site effects on the sedimentary layers, which in turn significantly influence earthquake ground motions in the area. Mapping of site response using microtremor measurements compared with geological and borehole data from Al Khobar City is the main objective of this work. The resonance frequency and the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The numerous tests of great soil samples of near-surface in the study area through several ground investigations showed that the nature of the land changes sideways and vertically, which reflects the presence of cavities or weakness zones throughout the study area at various depths and with different characterizations. These features naturally occur in such types of limestone rocks and calcareous soils (Alharbi et al, 2015;Al-Malki et al, 2015;Fnais et al, 2015;Alyousef et al, 2015a and;2015b).…”
Section: Resultsmentioning
confidence: 99%
“…The numerous tests of great soil samples of near-surface in the study area through several ground investigations showed that the nature of the land changes sideways and vertically, which reflects the presence of cavities or weakness zones throughout the study area at various depths and with different characterizations. These features naturally occur in such types of limestone rocks and calcareous soils (Alharbi et al, 2015;Al-Malki et al, 2015;Fnais et al, 2015;Alyousef et al, 2015a and;2015b).…”
Section: Resultsmentioning
confidence: 99%
“…The age of the Cenozoic magmatic rocks of the Arabian margin lies between late Oligocene (about 30 Ma) and Quaternary (about 5 ka) ( Fig. 4) (Camp and Roobol 1992;Bosworth et al 2005;Al-Amri et al 2012;Runge et al 2016). In the Arabian margin a few historical eruptions are documented (Moufti et al 2013) and present day magmatic activity is the cause of earthquakes linked to extensional tectonics (Pallister et al 2010;Koulakov et al 2014).…”
Section: Red Sea Rifting-related Magmatismmentioning
confidence: 99%
“…The surface geology of eastern Saudi Arabia is composed of consolidated and unconsolidated sediments. The consolidated sediments are of Palcocene to middle Eocene and Miocene to Piocene age, while the unconsolidated materials include Quaternary sabkha deposits, gravels, sands, and clays (AlHarbi, et al, 2015). Research is to be conducted using our extensive geotechnical engineering laboratory, and existing local in situ and laboratory data.…”
Section: Geotechnical Engineeringmentioning
confidence: 99%